Lesser-Consumed Tropical Fruits and Their by-Products: Phytochemical Content and their antioxidant and anti-inflammatory potential. - Abraham, Wall-Medrano (2022)
çaí, lychee, mamey, passion fruit and jackfruit are some lesser-consumed tropical fruits due to their low commercial production. In 2018, approximately 6.8 million tons of these fruits were harvested, representing about 6.35% of the total world production of tropical fruits. The present work reviews the nutritional content, profile of bioactive compounds, antioxidant and anti-inflammatory capacity of these fruits and their by-products, and their ability to modulate oxidative stress due to the content of phenolic compounds, carotenoids and dietary fiber. Açaí pulp is an excellent source of anthocyanins (587 mg cyanidin-3-glucoside equivalents/100 g dry weight, dw), mamey pulp is rich in carotenoids (36.12 mg β-carotene/100 g fresh weight, fw), passion fruit peel is rich in dietary fiber (61.16 g/100 dw). At the same time, jackfruit contains unique compounds such as moracin C, artocarpesin, norartocarpetin and oxyresveratrol. These molecules play an important role in the regulation of inflammation via activation of mitogen-activated protein kinases (including p38, ERK and JNK) and nuclear factor κB pathways. The properties of the bioactive compounds found in these fruits make them a good source for use as food ingredients for nutritional purposes or alternative therapies. Research is needed to confirm their health benefits that can increase their marketability, which can benefit the primary producers, processing industries (particularly smaller ones) and the final consumer, while an integral use of their by-products will allow their incorporation into the circular bioeconomy.